SYNCHRONIZATION OF OVULATION IN POSTPARTUM SAHIWAL COWS - ALl, SARFRAJ; AWASTHl, M K; KHAN, J R; TIWARl, R P; BHONSLE, D; POYAM, M R (The Indian Journal of Animal Reproduction, 2023)
Present investigation was conducted to evaluate two different Ovsynch protocols for synchronization ofovulation in postpartum Sahiwal cows. Experimental animals (n=12) were randomly divided in to 2 groups; eachgroup consisted of 6 animals. Animals of group I were treated with traditional Ovsynch protocol, while animals ofgroup II were treated with a modified Ovsynch protocol where first GnRH injection was replaced with hCG. Treatedanimals were inseminated at fixed time of 14 to 20 hrs after second GnRH injection without estrus detection.Blood sample were collected from the experimental animals on days -10, 0, 8 and 16 of Ovsynch protocol (day60postpartum = day O of Ovsynch protocol) to estimate serum progesterone concentrations. Animals were classifiedas cyclic (n=8, P4 e" 1ng/ml) and acyclic (n=4, P4 < 1ng/m1) based on serum progesterone concentration on days-10 and 0. Response to treatment was assessed in treated animals on the basis of progesterone concentration onday 8 (PG treatment); 83.3% (5/6) animals responded to first GnRH treatment in group I and 100% (6/6) animalsresponded to hCG treatment in group II. Two cyclic animals each from both the treatment groups got conceived tofixed time Al giving conception rate of 40% (2/5) in group I and 33.3% (2/6) in group II. Three cyclic and 4 acyclicanimals did not conceive after responding to treatment, while one cyclic animal did not respond to first GnRHtreatment. No any beneficial effect of replacing first GnRH injection with hCG could be obtained in ovulationsynchronization and conception rate with Ovsynch protocol in Sahiwal cows during early postpartum period
Keywords: Cows; Postpartum; Sychronlzation; Ovulation; Ovsynch